Body content of selenium in coeliac disease. Issue 6434 (23rd June 1984) - Hinks, L J; Inwards, K D; Lloyd, B; Clayton, B E
Abstract : Concentrations of selenium in whole blood, plasma, and leucocytes were determined in 16 patients with coeliac disease confirmed by biopsy and 32 controls. All the patients were clinically well and receiving gluten free diets. The concentrations of selenium were significantly lower in the leucocytes, blood, and plasma of patients compared with controls, probably indicating a decrease in the body content of selenium. A high incidence of malignancy in coeliac disease has been reported. As a protective role for selenium against cancer has been postulated, the importance of this unexpected observation of lowered tissue concentrations of selenium requires further investigation.